Genomics, proteomics, and the nervous system - Clelland, James D. (Advances in neurobiology, 2011)
The potential for malfunction of this large number of complex biological systems is great, leading to the many behavioral and cognitive deficits observed in human psychiatric and neurological disorders. Genomics, Proteomics, and the Nervous System discusses research designed to increase our understanding of the nervous system and its structures and activities. This volume of Advances in Neurobiology discusses the utilization of genomic and proteomic technologies, to address facets of neurobiology including development and epigenetic regulation, functions in learning and memory, and changes associated with neurological and psychiatric disorders.